Image-Based Modeling - Quan, Long.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
This book guides you in the journey of 3D modeling from the theory with elegant mathematics to applications with beautiful 3D model pictures. Written in a simple, straightforward, and concise manner, readers will learn the state of the art of 3D reconstruction and modeling. Professor Takeo Kanade, Carnegie Mellon University About this book: The computer vision and graphics communities use different terminologies for the same ideas This books provides a translation, enabling graphics researchers to apply vision concepts, and vice-versa Independence of chapters allows readers to directly jump into a specific chapter of interest Compared to other texts, gives more succinct treatment overall, and focuses primarily on vision geometry Image-Based Modeling is for graduate students, researchers, and engineers working in the areas of computer vision, computer graphics, image processing, robotics, virtual reality, and photogrammetry. About the Author: Long Quan is a Professor of the Department of Computer Science and Engineering at the Hong Kong University of Science and Technology. He received a Ph.D. degree in Computer Science from INRIA, and has been a CNRS researcher at INRIA. Professor Quan is a Fellow of the IEEE Computer Society.
Geometry: fundamentals of multi-view geometry -- Geometry prerequisite -- Multi-view geometry -- Computation: from pixels to 3D points -- Feature point -- Structure from Motion -- Modeling: from 3D points to objects -- Surface modeling -- Hair modeling -- Tree modeling -- Façade modeling -- Building modeling.
Keywords: Computer science; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Graphics; Signal, Image and Speech Processing; Image Processing and Computer Vision; Pattern Recognition